SUPGUARD (CIPEEX, 2025)
SUPGUARD: MORE SECURITY AT YOUR FINGERTIPSSupGuard is a security application designed to enhance public safety in Anápolis, Goiás, by providing real-time alerts and an interactive risk map based on user-reported incidents. The project aims to offer a practical, scalable solution for crime prevention and awareness within the community. The method relies on crowdsourced data collection, where users can report incidents, which are then processed and displayed on a dynamic map showing risk zones. These zones are color-coded according to severity: red for high-risk, orange for medium-risk, yellow for moderate-risk, and green for low-risk areas. By offering both a free and a premium version, SupGuard allows users to access basic functionalities at no cost, while advanced features such as detailed analyses and notification customization are available for paid users. The system operates without intrusive advertisements, ensuring that notifications remain clear and undistracted, especially during emergencies. The results anticipated from this model include greater public awareness, quicker response times to potential threats, and an overall reduction in crime due to informed, proactive behavior from users. Although SupGuard initially focuses on the local community, its framework provides an opportunity for future governmental collaboration, potentially integrating law enforcement for enhanced public security. The conclusions highlight the necessity of such a service in areas without existing technological solutions for real-time crime reporting, positioning SupGuard as a valuable tool for both residents and visitors.
Keywords: Crime; Security; Crowdsourcing